2022
DOI: 10.3390/ma15020607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcination Temperature on Mechanical Properties of Magnesium Oxychloride Cement

Abstract: In order to make full use of magnesium chloride resources, the development and utilisation of magnesium oxychloride cement have become an ecological and economic goal. Thus far, however, investigations into the effects on these cements of high temperatures are lacking. Herein, magnesium oxychloride cement was calcinated at various temperatures and the effects of calcination temperature on microstructure, phase composition, flexural strength, and compressive strength were studied by scanning electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This also shows that basalt fibres did not play any significant role in retaining compressive strength. A comparison with a recent study by Chang et al [26] in Figure 5b further highlights the effectiveness of the addition of fibres in enhancing elevated temperature resistance. Mix M1.5BF0.5PP exhibited substantially higher residual compressive strength especially A comparison with a recent study by Chang et al [26] in Figure 5b further highlights the effectiveness of the addition of fibres in enhancing elevated temperature resistance.…”
Section: Mechanical Performance Of Frmocc At Elevated Temperatures Co...supporting
confidence: 62%
See 1 more Smart Citation
“…This also shows that basalt fibres did not play any significant role in retaining compressive strength. A comparison with a recent study by Chang et al [26] in Figure 5b further highlights the effectiveness of the addition of fibres in enhancing elevated temperature resistance. Mix M1.5BF0.5PP exhibited substantially higher residual compressive strength especially A comparison with a recent study by Chang et al [26] in Figure 5b further highlights the effectiveness of the addition of fibres in enhancing elevated temperature resistance.…”
Section: Mechanical Performance Of Frmocc At Elevated Temperatures Co...supporting
confidence: 62%
“…However, research in this specific area is scarce. Recently, Chang et al [26] evaluated the fire performance of pure MOC mix and found a significant deterioration in both compressive and flexural strength as the temperature increased from 100 to 500 • C. While this indicates poor performance, there is still insufficient evidence to conclusively affirm the suitability of MOC for fire-resistant applications, especially the recently formulated water-resistant MOC matrix which incorporates other additives such as FA and phosphates. This MOC matrix possesses more hydration phases than just Phase 5 and Phase 3 and hence, there is uncertainty about the role of additional binders in fire resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the fire-resisting mechanism of MOC, there is very limited literature available, and the complete understanding of its mechanism is still uncertain and needs further investigation. Chang et al [110] conducted a study on the elevated temperature behavior of pure MOC mixes, noting a complete loss in compressive and flexural strength as temperatures rose from 100 to 500 • C. To enhance the elevated temperature performance of MOC, Rawat et al [35] investigated the incorporation of hybrid fibers (basalt fiber and polypropylene fiber) into MOC. Results showed a substantial deterioration in compressive strength, ranging from approximately 30% to 87% at 400 • C and over 95% at 800 • C (Figure 12), with no observed cracks or spalling.…”
Section: Application Of Moc As a Fire-resistive Materialsmentioning
confidence: 99%
“…MOC is a mixture of magnesium oxide (MgO) and magnesium chloride (MgCl 2 ) along with water, which hardens in air. Its raw material, magnesium chloride, can be derived from further processing of salt lake waste, while magnesium oxide is derived from the calcination of dolomite or magnesite. Unlike silicate cement clinker, magnesite can be calcined at 600–1300 °C to obtain the activated magnesium oxide, which can be used to manufacture MOC. , Therefore, the development and use of MOC does not only reduce energy consumption and CO 2 emissions but also further increase the recycling of waste to alleviate the global warming crisis. Unlike calcium silicate hydrate (C–S–H) or calcium aluminum silicate hydrate (C-A–S-H) of silicate cement, , the main physical structures of MOC are 3-phase, 5-phase, 2-phase, and 9-phase, , where the main phases present at room temperature are 3-phase and 5-phase, and they improve the mechanical strength of MOC composites in the form of needle rods and short rods.…”
Section: Introductionmentioning
confidence: 99%